Freshly isolated hepatocyte transplantation in acetaminophen-induced hepatotoxicity model in rats - Rodrigues,Daniela (2012)
CONTEXT: Hepatocyte transplantation is an attractive therapeutic modality for liver disease as an alternative for orthotopic liver transplantation. OBJECTIVE: The aim of the current study was to investigate the feasibility of freshly isolated rat hepatocyte transplantation in acetaminophen-induced hepatotoxicity model. METHODS: Hepatocytes were isolated from male Wistar rats and transplanted 24 hours after acetaminophen administration in female recipients. Female rats received either 1x10(7) hepatocytes or phosphate buffered saline through the portal vein or into the spleen and were sacrificed after 48 hours. RESULTS: Alanine aminotransferase levels measured within the experiment did not differ between groups at any time point. Molecular analysis and histology showed presence of hepatocytes in liver of transplanted animals injected either through portal vein or spleen. CONCLUSION: These data demonstrate the feasibility and efficacy of hepatocyte transplantation in the liver or spleen in a mild acetaminophen-induced hepatotoxicity model.